Computational Simulation of the Random Depolymerization of Linear Polymers Obtained by Step-Polymerization of AB-type Monomers - López, Floralba; Rangel, Geraldine; Uzcategui, Mayerlin; Velásquez, Cristóbal Lárez (Journal of Research Updates in Polymer Science, 2013)
This paper presents evaluation results of a computational algorithm developed to simulate the random depolymerization process of a linear polymer having an initial distribution of molecular weights similar to polymers obtained by polycondensation of AB-type monomers, i.e., Flory-Schultz or most probable distribution. Starting from fundamental definitions of this system, as the initial values of the degree of polymerization and chain number (Xno and No, respectively) and the percentage of cleaved bonds (%E), it is confirmed that our algorithm adequately describes the random depolymerization process. Results obtained during the computational simulation indicate that the algorithm properly predicts, among other things, that the inverse of the final polymerization degree (1/Xnf) increases linearly with the applied %E while polydispersity after depolymerization (Df) decreases linearly when the latter parameter increases.